Kenduri Sko Tradition In The Community Adat Depati Rencong Telang Pulau Sangkar Kerinci Regency - Azoni, Liza (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
This study aims to investigate how the indigenous people of Depati Rencong Telang Pulau Sangkar at Kerinci Regency conduct the Kenduri Sko Tradition. The Kenduri Sko tradition is a traditional ceremony that was carried out 1 (one) time in 1-5 years in the indigenous people of Rencong Telang Pulau Sangkar. The Kenduri Sko ceremony is used for the Depati Ninik Mamak coronation ceremony, the purification of heirloom objects, and the kenduri after harvest (kenduri Tuai). This study is qualitative research and was conducted in Pulau Sangkar Village Batang Merangin Subdistrict Kerinci Regency, using the interview method. For some respondents, data gathering methods include observation, interviewing, and documentation. The following are the study's hypotheses: (1) the practice of applying the Kenduri Sko tradition is customary; (2) the implementation process of kenduri sko. 3) the Kenduri Sko Tradition contains sacred values. The results of this study describe how the Kenduri Sko Tradition is implemented, specifically a traditional ceremony for the inaguration or coronation of the Depati Ninik Mamak and Hulubalang. This is followed by complementary events such as cooking together, eating together, single orgen, singing, and dancing. Finally, at the culminating event, the last night closed with a performance of Tauh Ritual Dance. An ancestral dance known as the Tauh Ritual Dance is still practiced and performed at the Kenduri Sko ceremony until this day. And the author also describes the values contained in the Kenduri Sko Tradition in the indigenous people of Depati Rencong Telang Pulau Sangkar.